2015
DOI: 10.1038/cr.2015.145
|View full text |Cite|
|
Sign up to set email alerts
|

Dicer-independent RNA-directed DNA methylation in Arabidopsis

Abstract: RNA-directed DNA methylation (RdDM) is an important de novo DNA methylation pathway in plants. Small interfering RNAs (siRNAs) generated by Dicers from RNA polymerase IV (Pol IV) transcripts are thought to guide sequence-specific DNA methylation. To gain insight into the mechanism of RdDM, we performed whole-genome bisulfite sequencing of a collection of Arabidopsis mutants, including plants deficient in Pol IV (nrpd1) or Dicer (dcl1/2/3/4) activity. Unexpectedly, of the RdDM target loci that required Pol IV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 67 publications
8
103
2
1
Order By: Relevance
“…The overall results showed that the fruit could be a potential source of sugar, flavonoid and total fat. The results are in good agreement with the reported literature [33,34].…”
Section: Resultssupporting
confidence: 83%
“…The overall results showed that the fruit could be a potential source of sugar, flavonoid and total fat. The results are in good agreement with the reported literature [33,34].…”
Section: Resultssupporting
confidence: 83%
“…3) were evaluated for significance using a block-bootstrap method. 58 The Class F loci showed significant overlap with all histone modifications, with particularly large numbers of overlaps being observed with H3K27me1 and K3K9me2, in line with observations made by Yang & Zhang et al, 59 who also identified overlap between these histone marks and DCL-independent methylation. The apparent constitutive heterochromatin at the F loci may account for the dependence of CHG F type loci on DDM1.…”
Section: Classes Of Interaction and Histone Modificationsupporting
confidence: 72%
“…We found that most classes of sRNA loci are enriched for overlap with H3K9me2 and H3K27me1, recently identified as enriched within subclasses of RdDM loci. 59 The C24-specific sRNAs do not show this enrichment, likely due to differences between loci of histone modifications between ecotypes.…”
Section: Classes Of Interaction and Histone Modificationmentioning
confidence: 99%
“…The relative histone modification abundance was defined as n(Histone) 3 N(Input)/(N(Histone) 3 n(Input)), where n() is the sum of the reads in the TSS-surrounding regions and N() is the number of all the mapped reads. Histone and Input represent the specific histone modification and ChIP input, respectively (Yang et al, 2016).…”
Section: Defining the Ortholog Relationshipmentioning
confidence: 99%